Technology Entrepreneurship Project (ENT 600) : Starbucks Corporation / Khairul Naeem Hassim - Hassim, Khairul Naeem (2021)
Starbucks Corporation is an American multinational chain of coffeehouses and roaster reserves headquartered in Seattle, Washington. It was founded in 1971 by Jerry Baldwin, Zev Siegel, and Gordon Bowker in Seattle, Washington. Howard Schultz was the key person who turned the company a huge success around the globe. Since the beginning Starbucks has been facing many tough challenges and yet it is still remains as the best coffee House in the world. From this study, I can learn about analysing, applying insight, reasoning and drawing conclusions in order to understand this company even more. The first part of this case study has been focusing on collecting the company information such as the background of the company, the problem statement and the purpose of the study. The second part of the case study focuses on its’ background, organizational structure, products and services, technology, business, marketing and operational strategy. We only use SWOT, which is the short form for strength, weaknesses, opportunities and threats of this company in order to analyze the product or services of the company and to understand more on how the company works. The discovery of such problems leads to improvements or finding a way out to make it smooth and straightforward. There commendations also come from findings and discussions. This provides an opportunity for the development of new products with better versions to customers and companies.